High-Resolution Melting Curve Analysis of the 16S Ribosomal Gene to Detect and Identify Pathogenic and Saprophytic Leptospira species in Colombian Isolates (2017)
ABSTRACT: It is important to identify the circulating Leptospira agent to enhance the performance of serodiagnostic tests by incorporating specific antigens of native species, develop vaccines that take into account the species/serovars circulating in different regions, and optimize prevention and control strategies. The objectives of this study were to develop a polymerase chain reaction (PCR)–high-resolution melting (HRM) assay for differentiating between species of the genus Leptospira and to verify its usefulness in identifying unknown samples to species level. A set of primers from the initial region of the 16S ribosomal gene was designed to detect and differentiate the 22 species of Leptospira. Eleven reference strains were used as controls to establish the reference species and differential melting curves. Twenty-five Colombian Leptospira isolates were studied to evaluate the usefulness of the PCR–HRM assay in identifying unknown samples to species level. This identification was confirmed by sequencing and phylogenetic analysis of the 16S ribosomal gene. Eleven Leptospira species were successfully identified, except for Leptospira meyeri/ Leptospira yanagawae because the sequences were 100% identical. The 25 isolates from humans, animals, and environmental water sources were identified as Leptospira santarosai (twelve), Leptospira interrogans (nine), and L. meyeri/L. yanagawae (four). The species verification was 100% concordant between PCR–HRM and phylogenetic analysis of the 16S ribosomal gene. The PCR–HRM assay designed in this study is a useful tool for identifying Leptospira species from isolates.